"The truest form of patriotism" : pacifist feminism in Britain, 1870-1902 - Brown, Heloise (Gender in history., 2003)
This fascinating book explores the pervasive influence of pacifism on Victorian feminism. Drawing on previously unused source material, it provides an account of Victorian women who campaigned for peace and the many feminists who incorporated pacifist ideas into their writing on women and gender.